Obtenção e caracterização térmica de compósitos nanoestruturados de resina fenol-furfurílica/CNT - Conejo, Luíza dos Santos [UNESP] (2015)
Phenolic and furfuryl alcohol resins have a high density of cross-links and high carbon yield, and thus widely applied in the aerospace area, mainly in the vitreous carbon processing. The production of phenol-furfuryl alcohol resin (FF) is already available in the literature, however, few works report its properties. Furthermore, almost no information can be found regarding the production of nanostructured composites of FF/carbon nanotubes (CNT). In this way, the aim of this work is to obtain nanostructured composites of FF/CNT with different concentrations of carbon nanotubes (0.1, 0.5 and 1.0% w/w) and thermal characterization. The specimens were evaluated by differential scanning calorimetry (DSC), in order to obtain information regarding your specific heat (cp); thermo-mechanical analysis (TMA) for obtaining the linear thermal expansion coefficient (α) and thermogravimetry (TGA) to knowledge of the temperature of thermal degradation, either by actual analyses as simulated by software known as Highway Simulation. The DSC analysis shows that the samples studied show that cp values tend to increase with the increase of temperature up to 150°C. Furthermore, the introduction of the CNT in FF resin increases the value of cp up to a concentration of 0.5%. The coefficient of linear thermal expansion obtained by the TMA technique for sample FF was 33.10-6 °C-1. The introduction of the CNT samples FF does not affect its thermal stability. The values found in the analyses are close to the values of the phenolic resin in the literature